Doughnut of social and planetary boundaries monitors a world out of balance - Andrew L. Fanning; Kate Raworth (Nature, 2025)
Abstract The doughnut-shaped framework of social and planetary boundaries (the ‘Doughnut’) provides a concise visual assessment of progress towards the goal of meeting the needs of all people within the means of the living planet1–3. Here we present a renewed Doughnut framework with a revised set of 35 indicators that monitor trends in social deprivation and ecological overshoot over the 2000–2022 period. Although global gross domestic product (GDP) has more than doubled, our median results show a modest achievement in reducing human deprivation that would have to accelerate fivefold to meet the needs of all people by 2030. Meanwhile, the increase in ecological overshoot would have to stop immediately and accelerate nearly two times faster towards planetary boundaries to safeguard Earth-system stability by 2050. Disaggregating these global findings shows that the richest 20% of nations, with 15% of the global population, contribute more than 40% of annual ecological overshoot, whereas the poorest 40% of countries, with 42% of the global population, experience more than 60% of the social shortfall. These trends and inequalities reaffirm the case for overcoming the dependence of nations on perpetual GDP growth4,5 and reorienting towards regenerative and distributive economic activity—within and between nations—that assigns priority to human needs and planetary integrity.